Copeptina como marcador de estresse em crianças vítimas de maus-tratos - Coelho, Roberta Paula Schell (2014)
Introduction: Studies have shown that childhood maltreatment (CM) can be considered one of the most serious and chronic types of psychological stress. Although researches have reported CM as a risk factor for many diseases, studies about CM biomarkers remains underexplored. Objective: Verify the association between CM and biomarkers, specially copeptin, and behavioral changes. Method: This dissertation consists of three studies. The first study is a review of CM neurobiology. The second study presented a systematic review regarding the correlation between childhood maltreatment and inflammatory markers in adulthood. The third study investigated serum copeptin levels in children with and without history of CM. Results: The first study highlights the impact of CM as being a geneenvironment interaction resultant that seems to modulate the neurobiological cascade connected to vulnerabilities and resilience of each individual. Survivors of CM can exhibit alterations in several physiological systems, including the immune, endocrine, cardiovascular, behavioral, and central nervous systems. Childhood trauma is associated with increased autonomic stress responses and reprogramming of glucocorticoid signaling, thus contributing to exaggerated stress and immune responsiveness. There is strong evidence of the association between CM and abnormalities in the immunoendocrine system. In the systematic review study we analyzed 19 articles about the topic. Studies showed that a history of CM was associated with increased levels of C-reactive protein, fibrinogen and proinflammatory cytokines. CM seems to be related with a chronic inflammatory state independent of clinical comorbidities. The third study demonstrated that CM is correlated to increased copeptin serum levels and it is non-related to age, sex and psychopathology symptoms. Furthermore, the copeptin can be considered a promising novel biomarker in CM. Conclusions: The present thesis presents new and promising data regarding biological markers and CM that corroborates with the current literature findings. The data shown here introduces copeptin as a new potential biomarker associated to CM. This thesis also reinforces the presence of neuro-immune-endocrine alterations in individuals presenting CM history. The literature shows CM systematically impacts the physical and mental health, potentializing the development and complications risks of many other diseases. So, it is of extreme importance to investigate these biological mechanisms that seems to be correlated to environmental factors